Gaya Bahasa Simile dalam Kumpulan Puisi Balada Orang-Orang Senja Karya Sobirin Zaini - Sri Rahayu; Muliana Muliana; Nanda Zuliana; Rita Silpina; Syah Rani Pane; Yoga Satria; Zikry Jawilovia (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research is motivated by the importance of using simile language styles in Sobirin Zaini's collection of poetry ballads of twilight people. The aim of this research is to describe, analyze and interpret the ballad poetry of the twilight people by Sobirin Zaini. The method in this research is descriptive with a qualitative approach. The data source in this research is a collection of poetry ballads of twilight people by Sobirin Zaini. The data collection technique used in this research is using hermeneutic techniques consisting of reading, taking notes, and concluding. With the data analysis steps as follows: 1. Classifying the data according to the research problem, 2. Analyzing the data, 3. Interpreting the results of research on language styles put forward by Henry Guntur Tarigan in (2013). After analyzing the data, it was found that the results of research on simile language style in the collection of ballad poetry of people at dusk by Sobirin Zaini, that in the collection of poetry the quality of poetry is illustrated from the aspect of simile language style and 18 simile data were found in 18 poems in the Poetry Collection of People's Ballads. -The Twilight People by Sobirin Zaini. The similes that are dominantly used are similes like. The least used similes are as and as, the unused similes are similes like, like, like, for example, penaka, similar.